Excavations on Tòrr an Aba, Iona, Argyll - Fowler, Elizabeth; Fowler, P J (Proceedings of the Society of Antiquaries of Scotland, 1989)
Excavations (1956-7) on a rock outcrop immediately west of Iona Abbey revealed a sub-rectangular building and a later cross-base. The possible identification of the building with one of the cells of St Columba is considered. Au (abr)